Thermosonication-enhanced bioaccessibility and functional quality of dill juice: an in vitro digestion approach - Yıkmış, Seydi; Ateş, Abdullah; Demirel, Selinay; Levent, Okan; Tokatlı, Nazlı; Demirok, Nazan Tokatlı; Aljobair, Moneera O.; Karrar, Emad; Althawab, Suleiman A.; Mohamed Ahmed, Isam A. (Frontiers in Nutrition, 2025)
The effects of thermosonication — a non-thermal method considered an alternative to conventional thermal treatments — on the functional components in dill (Anethum graveolens) juice were comprehensively investigated in this study, as well as the post-digestion bioaccessibility levels of these components. In this study, samples from three different treatment groups— thermosonicated (TS-DJ), control (CDJ), and thermally pasteurized (P-DJ) were compared in terms of key parameters such as total chlorophyll content, total phenolic content (TPC), iron reducing capacity (FRAP), and β-carotene. Additionally, a controlled in vitro digestion system was used to analyze the stability and recovery rates of bioactive substances and volatile aroma compounds at different stages of the digestion process (gastric, oral, and intestinal phases). The findings revealed that thermosonication was highly effective in preserving the bioactive components both at the initial level and during the 21-day storage period and significantly increased their post-digestion bioaccessibility levels. Optimization of application parameters was achieved using a combination of Equilibrium Optimization algorithms and Response Surface Methodology (RSM), and the resulting prediction models were validated with high statistical confidence. The Pearson correlation analysis revealed significant positive correlations among β-carotene, characteristic volatile compounds, and total phenolic compounds. This suggests that the increase in these bioactive compounds may be directly related to the improvement in the aroma profile of dill juice. The data obtained indicate that thermosonication may offer an effective alternative to conventional thermal treatments in enhancing the functional quality of dill juice and its post-digestive bioaccessibility. However, further studies are needed to assess its potential for consumer acceptance and industrial integration. In this context, the study reveals important findings that will help develop new technologies for processing plant-based beverages.